2004
DOI: 10.1590/s0036-46652004000400004
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendroglioma in a patient with AIDS: case report and review of the literature

Abstract: SUMMARYIn the last years, new techniques of neuroimages and histopathological methods have been added to the management of cerebral mass lesions in patients with AIDS. Stereotactic biopsy is necessary when after 14 days of empirical treatment for Toxoplasma gondii encephalitis there is no clinical or neuroradiologic improvement. We report a woman with AIDS who developed a single focal brain lesion on the right frontal lobe. She presented a long history of headache and seizures. After two weeks of empirical tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This case illustrate that glial tumors, including gliosarcoma, should be considered in the differential diagnosis of brain masses in HIV-seropositive patients 12 . Early stereotactic biopsy is needed to establish the final diagnosis of these tumors and is recommended by many authors 12,13 .…”
Section: Discussionmentioning
confidence: 85%
“…This case illustrate that glial tumors, including gliosarcoma, should be considered in the differential diagnosis of brain masses in HIV-seropositive patients 12 . Early stereotactic biopsy is needed to establish the final diagnosis of these tumors and is recommended by many authors 12,13 .…”
Section: Discussionmentioning
confidence: 85%
“…Approximately 40% to 60% of patients with AIDS develop some neurological disorder at some stage of the disease 4 . Acute exacerbation of chronic Chagas' disease can occur in immunocompromised patients, especially in individuals with the involvement of cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that over 50% of Americans suffering from AIDS brave neurological complications 1–3. Although the more common brain lesions associated with AIDS are due to the central nervous system (CNS) lymphomas, toxoplasma encephalitis or progressive multifocal leucoencephalopathy (PML),4 relatively recent clinical evidence has shown that AIDS-independent cerebral tumours5 can arise as well, albeit less commonly. Previous incidents have been reported with HIV and AIDS patients presenting with cerebral astrocytomas6 (table 1), with only one case of a brainstem glioblastoma multiforme (GBM) reported in Germany in 2002 7.…”
Section: Introductionmentioning
confidence: 99%